THE INFLUENCE OF BRAND AMBASSADOR AND SOCIAL MEDIA MARKETING ON PURCHASE DECISIONS OF ORTUSEIGHT FUTSAL SHOES(CASE STUDY ON FUTSAL ATHLETES IN INDONESIA, MALAYSIA, AND THAILAND) - Vita Wafiq Azizah; Ayuningtyas Yuli Hapsari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze the influence of brand ambassador and social media marketing on the purchase decision of Ortuseight futsal shoes among futsal athletes in Indonesia, Malaysia, and Thailand. Using a quantitative approach, data were collected through an online survey of 100 futsal athletes in Indonesia, Malaysia, and Thailand who are familiar with or have used Ortuseight products. Multiple linear regression analysis with SPSS version 27 was employed. The findings reveal that partially, brand ambassador has no significant effect on purchase decision (t-count 0.623 < t-table 1.984, sig. 0.535 > 0.05). Social media marketing also has no significant effect on purchase decision (t-count -0.025 < t-table 1.984, sig. 0.980 > 0.05). Simultaneously, brand ambassador and social media marketing have no significant effect on purchase decision (F-count 0.375 < F- table 3.09, sig. 0.688 > 0.05) with an Adjusted R Square value of only 0.8%. These results highlight that fundamental factors such as product quality, specifications, comfort, durability, and price are more dominant considerations for futsal athletes in making purchase decisions.